The Lighter Side of TEFL : A Teacher's Resource Book of Fun Activities for Students of English as a Foreign Language - United States Information Agency, Washington, DC. English Language Programs Div.; Kral, Thomas; United States Information Agency, Washington, DC. English Language Programs Div. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1994)
The guide provides teachers of English as a Foreign Language (TEFL) with classroom instructional activities that reinforce vocabulary or teach specific language skills (listening, speaking, reading, writing) while demonstrating that communicating in English can be fun. The activities are brief and self-contained, and an audiotape cassette (not included) is designed for use with the last four sections of the book. Each section focuses on a different type of activity: word games; crossword puzzles; idioms; limericks; jokes and riddles; puzzle stories; shaggy dog stories; and folk wisdom. An answer key is also included. (MSE)
Keywords: Class Activities; English (Second Language); Figurative Language; Folk Culture; Games; Humor; Idioms; Instructional Materials; Language Skills; Poetry; Puzzles; Second Language Instruction; Short Stories; Skill Development; Jokes -- Limericks -- Riddles; Guides, Classroom -- Teacher